Relevance of Jamal al Din al Afghani’s Political Thought to The Form of Government of Indonesian Republic - Izzatul Ulya (Program Studi Hukum Tata Negara Fakultas Syariah UIN Maulana Malik Ibrahim Malang, 2019)
Jamal al-Din al-Afghani as a figure in modern Islamic reforms that combines the ideas of Internationalism with Islam. In his ideas, Afghani rejected all Western penetration and anti-colonialism. As a result of Western penetration, absolutism and depotism emerged in the Islamic kingdoms at that time. For him, absolutism will only make the people fettered. However, Afghani did not completely reject Western thought. Afghani combined the teachings of Islam with the West which implicitly raised the form of Republican government through his ideas. In line with Afghani, Indonesia also adheres to a form of republican government that has the people's sovereignty. Both concepts of the republic have relevance as a form of republican government, namely democracy and people's involvement. The formulation of the problem in this research is twofold. First, how Jamal al Din al Afghani's political thinking about the form of Republican government. Second, how the relevance of Jamal al-Din al-Afghani's political thinking towards the form of government of the Republic of Indonesia. This research is a type of normative juridical research. This study uses a combination of legal approaches and conceptual approaches. Methods of data collection are primary legal materials and secondary materials collected by inventorying positive law and other relevant legal materials, library studies, grouping of legal materials, and analyzing them. Data processing methods used are organizing, editing, and analizing. The results of this study that, first, Jamal al Din al Afghani's thinking about republics, between them: the existence of 'limited government', the existence of principles of justice (adl) and consultation (shura), the idea of democracy, the existence of shura run by ahl hall al ' aqd or ahl syawkah, ahl hall al-'aqd must be experienced and morally good, Every community participates through syuro and elections, the establishment of parties, freedom of the press, and revolutions based on the power of the people. second, namely Afghani thinking is relevant to the form of government of the Republic of Indonesia. It's just that there is one Afghani point in contrast to Article 7B of the 1945 Constitution, namely the existence of people power. For him, to oppose absolutism must be through rebellion or bloodshed.